Thymidine kinase 1 expression in ovarian serous adenocarcinoma is superior to Ki-67: A new prognostic biomarker. Issue 6 (June 2017) - Wang, Jianjun; Liu, Qi; Zhou, Xiaodie; He, Yan; Guo, Qing; Shi, Qunli; Eriksson, Staffan; Zhou, Ji; He, Ellen; Skog, Sven
Cancer is a disease with abnormally proliferating cells and therefore proliferation rate is an important index for assessing tumour growth. Ki-67 is a commonly used proliferation marker considered to be an unfavourable prognostic marker in some tumors, while Thymidine kinase 1 (TK1) is an interesting proliferation marker because its levels are highly dependent on the growth stage of cells. To define the immunohistochemistry (IHC) expression of the TK1 in patients with ovarian serous adenocarcinoma and establish its potential role as a new biomarker for progressive disease, we analyzed the expression patterns of TK1 and Ki-67 in 109 patients with ovarian serous adenocarcinoma. TK1 and Ki-67 expression both showed a statistically significant correlation to MD Anderson Cancer Center (MDACC) grade, but not to age, tumour size, lymph node metastasis or pathological TNM (pTNM) stages. TK1 expression, MDACC grades, pathological stages and lymph node metastasis correlate to relapse incident rate and overall survival, but Ki-67 does not. Although TK1 expression, MDACC grade, pTNM stage and lymph node metastasis significantly correlate to relapse in the Cox univariate analysis, in the multivariate Cox analysis only TK1 expression and lymph node metastasis were independent prognostic factors. The overall survival also correlated significantly to TK1 expression, MDACC grade, pTNM stage and lymph node metastasis in the Cox univariate analysis. However, only the pTNM stage was found to be an independent prognostic factor for survival in the Cox multivariate analysis. Therefore, though TK1 expression was an independent prognostic factor for relapse, but not for survival, TK1 is a more informative expression than Ki-67 for LI, relapse and overall survival rates. Thus, when TK1 is combined with MDACC grading, pTNM staging and lymph node metastasis, IHC determination of TK1 expression may improve the overall prediction of prognosis in patients with ovarian cancer.